Stimuli-responsive controlled growth of mono- and bidimensional particles from basic zirconium sulfate hydrosols - Rosa, M. A. Alves [UNESP]; Sanhueza, C. S. S. [UNESP]; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Briois, V. (Amer Chemical Soc, 2008)
A thermostimulated sol-gel transition in a system prepared by mixing a ZrOCl(2) acidified solution to a hot H(2)SO(4) aqueous solution was studied by dynamic theological measurements and quasi-elastic light scattering. The effect of temperature and of molar ratio R(S) = [Zr]/[SO(4)] on the gelation kinetics was analyzed using the mass fractal aggregate growth model. This study shows that the linear growth of aggregates occurs at the early period of transformation, while bidimensional growth occurs at the advanced stage. The bidimensional growth can be shifted toward monodimensional growth by decreasing the aggregation rate by controlling the temperature and/or molar ratio R(S). EXAFS and Raman results gave evidence that the linear chain growth is supported by covalent sulfate bonding between primary building blocks. At the advanced stage of aggregation, the assembly of linear chains through hydrogen bonding gave rise to the growth of bidimensional particles.